Foliar bacteria and soil fertility mediate seedling performance: a new and cryptic dimension of niche differentiation. Issue 11 (November 2016) - Griffin, Eric A.; Traw, M. Brian; Morin, Peter J.; Pruitt, Jonathan N.; Wright, S. Joseph; Carson, Walter P.
Abstract: The phyllosphere (comprising the leaf surface and interior) is one of the world's largest microbial habitats and is host to an abundant and diverse array of bacteria. Nonetheless, the degree to which bacterial communities are benign, harmful, or beneficial to plants in situ is unknown. We tested the hypothesis that the net effect of reducing bacterial abundance and diversity would vary substantially among host species (from harmful to beneficial) and this would be strongly mediated by soil resource availability. To test this, we monitored tree seedling growth responses to commercial antibiotics among replicated resource supply treatments (N, P, K) in a tropical forest in Panama for 29 months. We applied either antibiotics or control water to replicated seedlings of five common tree species ( Alseis blackiana, Desmopsis panamensis, Heisteria concinna, Sorocea affinis, and Tetragastris panamensis ). These antibiotic treatments significantly reduced both the abundance and diversity of bacteria epiphytically as well as endophytically. Overall, the effect of antibiotics on performance was highly host specific. Applying antibiotics increased growth for three species by as much as 49% ( Alseis, Heisteria, and Tetragastris ), decreased growth for a fourth species by nearly 20% ( Sorocea ), and had no impact on a fifth species ( Desmopsis ). Perhaps more importantly, the degree to which foliar bacteria were harmful or not varied with soil resource supply. Specifically, applying antibiotics had no effect when potassium was added but increased growth rate by almost 40% in the absence of potassium. Alternatively, phosphorus enrichment caused the effect of bacteria to switch from being primarily beneficial to harmful or vice versa, but this depended entirely on the presence or absence of nitrogen enrichment (i.e., important and significant interactions). Our results are the first to demonstrate that the net effect of reducing the abundance and diversity of bacteria can have very strong positive and negative effects on seedling performance. Moreover, these effects were clearly mediated by soil resource availability. Though speculative, we suggest that foliar bacteria may interact with soil fertility to comprise an important, yet cryptic dimension of niche differentiation, which can have important implications for species coexistence.